Stock Split dan Pengaruhnya Pada Return Saham - Anggraeni, Rr Tini; Hayata, Akrim (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
This study aims to determine the effect of the stock split on the Return of each company's stock. The sample using 6 companies that conduct stock split corporation activity, recorded in Indeks Saham Syariah Indonesia (ISSI) consistently during period 2012-2016 and once joined in Jakarta Islamic Index (JII). This study uses multiple regression analysis as a tool of analysis. The result of the analysis shows that simultaneously Return On Assets (ROA), Total Assets Turnover (TATO), Earning Per Share (EPS) and Price Earning Ratio (PER) produces significant influence only on ASII and TLKM stock. Partially, Price Earning Ratio (PER) variable gives significant effect to ASII, SCMA, and TLKM stock returns. While the variable Earning Per Share (EPS) produces a significant influence on ICBP stock returns.